Philippine Development Report : Creating More and Better Jobs - World Bank (Washington, DC, 2014)
Accelerating inclusive growth - the type that creates more and better jobs and reduces poverty - is a key challenge for the Philippines. Instead of rising agricultural productivity paving the way for the development of a vibrant labor-intensive manufacturing sector and subsequently of a high-skill services sector, the converse has taken place in the Philippines. Agricultural productivity has remained depressed, manufacturing has failed to grow sustainably, and a low-productivity, low-skill services sector has emerged as the dominant feature of the economy. Lack of competition in key sectors, insecurity of property rights, complex regulations, and severe underinvestment by the government and the private sector have led to this growth pattern, which is not the norm in the East Asia region. This report analyzes the policy distortions that led to the country's weak employment record, highlights the unique window of opportunity where government, business, labor, and civil society can work together and agree on an agenda on job creation, and outlines a number of recommendations which the reform coalition can consider to put the country on an irreversible path of inclusive growth and address the jobs challenge.